2019
DOI: 10.1371/journal.pone.0217043
|View full text |Cite
|
Sign up to set email alerts
|

Trace minerals in tilapia fillets: Status in the United States marketplace and selenium supplementation strategy for improving consumer’s health

Abstract: This goal of this study was to highlight the importance of minerals in the diet of fish for meeting micronutrient requirements in the human diet. First arsenic, calcium, cadmium, copper, iron, molybdenum, magnesium, manganese, sodium, phosphorus, potassium, selenium, and zinc concentrations of twelve commercially available tilapia samples were measured. The nutritional value of fillets in regard to their mineral content were assessed to establish potential health benefits or risks for consumers. The health ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Due to numerous coenzyme functions, minerals play an important role in human health, growth and development, and disease prevention [ 14 ]. Studies on mineral accumulation in fish are essential for understanding the effects associated with the consumption of fish by humans [ 15 ]. However, the role of fish as a dietary source of minerals is poorly recognized and underevaluated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to numerous coenzyme functions, minerals play an important role in human health, growth and development, and disease prevention [ 14 ]. Studies on mineral accumulation in fish are essential for understanding the effects associated with the consumption of fish by humans [ 15 ]. However, the role of fish as a dietary source of minerals is poorly recognized and underevaluated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Se nutritional supplements have been widely used in fish production ( Barbosa et al., 2020 ; Farzad et al., 2019 ). In our previous research, we found that there is organic matter on the surface of SeNP ( Zhu et al., 2023 ), which explained that some proteins are attached to the surface of SeNP, and our further research shows that there are six kinds of selenoproteins on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…According to Farzad et al. (2019), Se is a valuable resource for including in functional feeds for aquaculture because it can promote health and growth as well as improving the quality of their meat for human consumption. According to these authors, supplementation of feed with organic Se can potentially produce fish with higher concentrations of Se.…”
Section: Discussionmentioning
confidence: 99%